Childcare workers experience many stressors and little recognition - Ludovica Gambaro; C. Katharina Spieß; Franz Westermaier (DIW Weekly Report, 2021)
Childcare workers are essential for both families and society at large, and their working conditions and pay are often a topic of discussion. Using new data spanning until the end of 2019 from the Socio-Economic Panel (SOEP) as well as a special SOEP additional survey in day care centers, this report shows how childcare workers view their occupation, day-to-day work, and pay. According to the data, childcare workers are less satisfied than elementary school teachers in almost every single area. In regard to their health, childcare workers have about the same satisfaction level as nurses. Well over half are moderately to heavily stressed as a result of time pressure at work and 81 percent experience stress due to what they perceive as inadequate pay. If presented with the option to change their weekly hours worked, most childcare workers would choose to reduce them. To improve the quality of the working environment and allow childcare workers to spend more contact time with children, an increase in the number of staff in day care centers is necessary. Such an increase would benefit childcare workers, children, families, and society at large. However, to achieve this, all governance actors-the Federal Government, states, municipalities, as well as day care employers-need to commit in a bolder and more coordinated way.
Keywords: J44; 330; Day care teacher; child care worker; life satisfaction; well-being